Renal denervation in heart failure with normal left ventricular ejection fraction. Rationale and design of the DIASTOLE (DenervatIon of the renAl Sympathetic nerves in hearT failure with nOrmal Lv Ejection fraction) trial. (December 2013) - Verloop, Willemien L.; Beeftink, Martine M.A.; Nap, Alex; Bots, Michiel L.; Velthuis, Birgitta K.; Appelman, Yolande E.; Cramer, Maarten‐Jan; Agema, Willem R.P.; Scholtens, Asbjorn M.; Doevendans, Pieter A.; Allaart, Cor P.; Voskuil, Michiel
<x xml:space="preserve">Abstract</x> Aim Increasing evidence suggests an important role for hyperactivation of the sympathetic nervous system (SNS) in the clinical phenomena of heart failure with normal LVEF (HFNEF) and hypertension. Moreover, the level of renal sympathetic activation is directly related to the severity of heart failure. Since percutaneous renal denervation (pRDN) has been shown to be effective in modulating elevated SNS activity in patients with hypertension, it can be hypothesized that pRDN has a positive effect on HFNEF. The DIASTOLE trial will investigate whether renal sympathetic denervation influences parameters of HFNEF. Methods DIASTOLE is a multicentre, randomized controlled trial. Sixty patients, diagnosed with HFNEF and treated for hypertension, will be randomly allocated in a 1:1 ratio to undergo renal denervation on top of medical treatment (n = 30) or to maintain medical treatment alone (n = 30). The primary objective is to investigate the efficacy of pRDN by means of pulsed wave Doppler echocardiographic parameters. Secondary objectives include safety of pRDN and a comparison of changes in the following parameters after pRDN: LV mass, LV volume, LVEF, and left atrial volume as determined by magnetic resonance imaging. Also, MIBG (metaiodobenzylguanidine) uptake and washout, BNP levels, blood pressure, heart rate variability, exercise capacity, and quality of life will be assessed. Perspective DIASTOLE is a randomized controlled trial evaluating renal denervation as a treatment option for HFNEF. The results of the current trial will provide important information regarding the treatment of HFNEF, and therefore may have major impact on future therapeutic strategies. Trail registration NCT01583881